Miskonsepsi Materi Genetika tentang Ekspresi Gen - Tomi Hidayat; Kasmiruddin Kasmiruddin (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2020)
This study aims to identify and see cases of genetic material misconceptions in class XII IPA SMA Negeri 09 Bengkulu City. This research is a descriptive study, the population in this study were all students of class XII Science SMA Negeri 09 Bengkulu City, totaling seven classes. The sampling technique was done by cluster sample and two classes were selected, namely class XII Natural Sciences 2 and class XII Natural Sciences 7. The total sample used was 91 students. Data collection techniques in this study were two-dimensional diagnostic test instruments consisting of 40 multiple choice questions with a level of confidence (CRI). The results showed there were students' misconceptions of Genetic material by 35.01%. Of the eight learning indicators there are three indicators with a high number of misconceptions, namely indicator 8 (describing the process of protein synthesis, 33.46%), indicator 5 (describing the structure of RNA, 36.84%), and indicator 2 (describing the relationship of cells, chromosomes , genes, with DNA, 37.45%). Based on the cognitive level of the test, students experienced the most misconceptions at C5 (evaluation, 41.94%). Conclusion, Misconceptions experienced by students in learning genetic material about gene expression are in 3 indicators which are the highest of 8 indicators, causes of misconception due to lack of reference sources or information, the concept of genetic substance concept that is abstract, many foreign terms, difficult language, and the unpreparedness of students in accepting material delivered by the teacher. Keywords: Gene Expression, Genetic Material, Misconception